Pengaruh Online Customer Review, Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian - Mita Istinawati; R.A. Nurlinda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study examines and analyzes the effect of online customer reviews, product quality and service quality simultaneously and partially on purchasing decisions. And knowing which variable is the most dominant in influencing purchasing decisions. The research approach used in this research is quantitative research. The criteria for selecting the sample in this study were those aged 17 and over who had bought and consumed Mie Gacoan for more than 6 months and were in the Bali region. Questionnaires were collected as many as 195 respondents, the data was then processed using multiple linear regression method. Based on the results of the analysis it is known that online customer review variables, product quality and service quality simultaneously have a positive effect on purchasing decisions. Partially online customer review variables, product quality and service quality have a positive effect on purchasing decisions. Furthermore, the results show that the online customer review variable is the most dominant variable influencing purchasing decisions